Utilization of Moringa Leaf Pudding as a Solution within the Germas Tating (Turirejo Community Movement to Combat Stunting) Program for Toddlers - Muhammad Afwan Romdloni; Rizki Amalia Elfita; Khiliah Navis; Ramadhani Vica Ainur Rahma (Journal of Health Community Service, 2024)
Stunting is a condition in which toddlers have a length or height below the standard for their age, reflecting chronic malnutrition. Various strategies have been implemented to address this issue, including the provision of complementary feeding (MP-ASI) using locally available food sources to ensure age-appropriate nutrient intake. According to the Auxiliary Public Health Center in Turirejo Village, Gresik Regency, the prevalence of stunting has declined in recent years; however, in 2022, 30 toddlers were still identified as stunted, making it a continuing public health concern. The intervention employed a structured approach consisting of problem identification, development of a problem-solving framework, pre-test assessment, health education and practical training, and post-test evaluation. As a practical solution, a demonstration of complementary food preparation using moringa (Moringa oleifera) leaves was conducted. Moringa leaves were processed into moringa pudding as a protein-rich supplementary food for stunted toddlers. Pre-test and post-test results were presented in percentage form, and differences in knowledge among mothers of toddlers and posyandu cadres regarding stunting, complementary feeding, and exclusive breastfeeding were analyzed using the Wilcoxon signed-rank test. The findings indicated a p-value < 0.05, demonstrating a significant improvement in knowledge after the educational session. Participants were able to prepare and serve moringa pudding according to the demonstrated recipe. This socialization and local food–based complementary feeding initiative serves as a community learning strategy to prevent further increases in stunting prevalence in Turirejo Village.